FILIAL PIETY IN THE PIOUS CHILD ACCORDING TO IMAM AL BUKHARI'SAL-ADAB AL-MUFRAD - Ruslinah Haji Yahanid; Mohd Rosmizi Abd Rahman; Muhammad Khairi Mahyuddinii (Universitas Sains Islam Al Mawaddah Warrahmah Kolaka, 2024)
Children are invaluable gifts from Allah to married couples and their families. Even before the child is born or the parents are married, the quest for the pious child begins with du’a, or supplication to Allah for a righteous child and protection against misguidance and idolatry. Nurturing and raising children is not an easy task. It is a huge responsibility to raise pious or righteous children in accordance with the Qur'an and Hadith. Raising and transforming these pious children into excellent Muslim-practicing adults is a more important but challenging task. Literature has shown that there have been many books regarding this pious child but the book of Imam al-Bukhari’s al-Adab al-Mufrad is a popular choice for most Muslims past and present. This article aims to highlight the qualities of the pious child taught by the Prophet PBUH and the Companions as in the said book regarding instilling filial piety by Imam Bukhari. The methodology used is the content analysis from a qualitative research methodology. The general findings show that the pious child is the righteous child who he believes and worships Allah subhanahu wa ta'ala (SWT) and believes and follows the sunnah of the Prophet Muhammad Peace Be Upon Him (PBUH). This pious child will promote filial piety, uphold good social etiquette, and mature into a responsible and respectable adult according to Islamic tenets.